Applying chaperones to protein-misfolding disorders: Molecular chaperones against α-synuclein in Parkinson's disease - Chaari, Ali; Hoarau-Véchot, Jessica; Ladjimi, Moncef (International journal of biological macromolecules, 2013)
•Refolding protein is the key for neurodegenerative disorder.•Protein chaperones can be a target for therapeutic intervention in Parkinson's disease.•The various molecular chaperones have a complementary effect in PD. Parkinson's disease (PD) is a neurodegenerative disorder characterized by the accumulation of a protein called α-synuclein (α-syn) into inclusions known as lewy bodies (LB) within neurons. This accumulation is also due to insufficient formation and activity of dopamine produced in certain neurons within the substantia nigra. Lewy bodies are the pathological hallmark of the idiopathic disorder and the cascade that allows α-synuclein to misfold, aggregate and form these inclusions has been the subject of intensive research. Targeting these early steps of oligomerization is one of the main therapeutic approaches in order to develop neurodegenerative-modifying agents. Because the folding and refolding of alpha synuclein is the key point of this cascade, we are interested in this review to summarize the role of some molecular chaperones proteins such as Hsp70, Hsp90 and small heat shock proteins (sHsp) and Hsp 104. Hsp70 and its co-chaperone, Hsp70 and small heat shock proteins can prevent neurodegeneration by preventing α-syn misfolding, oligomerization and aggregation in vitro and in Parkinson disease animal models. Hsp104 is able to resolve disordered protein aggregates and cross beta amyloid conformers. Together, these chaperones have a complementary effect and can be a target for therapeutic intervention in PD.